Effects of buoyancy forces on miscible liquid-liquid displacements in porous media. - Guo, Tianle. (University of Ottawa (Canada), 1994)
The effects of gravity forces on the miscible displacement of one fluid (aqueous glycerol solution) by another fluid (pure water) in a vertical consolidated porous medium have been investigated. A set of horizontal displacement experiments was performed for comparison with two sets of vertical-upward and vertical-downward displacements. It was found that gravitational forces (i.e. buoyancy forces) can be an important factor in determining the displacement pattern where fluids having different densities and different flowrates are involved. In a given porous medium system, the principal variables which affect the displacement efficiency of oil (or any other miscible liquid) by water are the viscosity ratio, density difference, and displacement flowrate. Increasing the viscosity ratio will decrease the oil recovery; however, when the viscosity ratio is close to unity, good oil recovery will be obtained. The injection flowrate is also critical. At low injection flowrates, the effects of gravity become relatively more important. At high flowrates, gravity forces have less effect on the displacement efficiency. In vertical-upward displacements, buoyancy forces play a negative role since they tend to promote viscous fingering and consequently lower the oil recovery (when $\rm \rho\sb{oil}>\rho\sb{water}$). On the other hand, in vertical-downward displacements, buoyancy forces tend to stabilize the displacement process, and high oil recoveries can be obtained. Comparing the horizontal displacement patterns with those of the two vertical displacements, it was found that buoyancy forces can exert very significant effects on fingering phenomena.
Keywords: Engineering, Chemical.